The role of fibrosis biomarkers in predicting the development of myocardial electrical instability (a literature review) - V. P. Ivanov; Yu. Yu. Shushkovska; I. V. Danylchuk; V. Р. Shcherbak; T. Yu. Tsybrii (Zaporožskij Medicinskij Žurnal)
The aim. To analyze scientific researches on studying the biomarkers of fibrosis based on a review of the most recent publications for the possibility to predict electrical myocardial instability development.